Heterogeneity in prevalence of subclinical Plasmodium falciparum and Plasmodium vivax infections but no parasite genomic clustering in the Chittagong Hill Tracts, Bangladesh - Huwe, T; Kibria, MG; Johora, FT; Phru, CS; Jahan, N; Hossain, MS; Khan, WA; Price, RN; Ley, B; Alam, MS; Koepfli, C (BioMed Central, 2022)
Background Malaria remains endemic in Bangladesh, with the majority of cases occurring in forested, mountainous region in the Chittagong Hill Tracts (CHT). This area is home to Bengali and diverse groups of indigenous people (Pahari) residing largely in mono-ethnic villages. Methods 1002 individuals of the 9 most prominent Pahari and the Bengali population were randomly selected and screened by RDT and qPCR. Parasites were genotyped by msp2 and deep sequencing of 5 amplicons (ama1-D3, cpmp, cpp, csp, and msp7) for Plasmodium falciparum (n = 20), and by microsatellite (MS) typing of ten loci and amplicon sequencing of msp1 for Plasmodium vivax (n = 21). Population structure was analysed using STRUCTURE software. Identity-by-state (IBS) was calculated as a measure of parasite relatedness and used to generate relatedness networks. Results The prevalence of P. falciparum and P. vivax infection was 0.7% by RDT (P. falciparum 6/1002; P. vivax 0/1002, mixed: 1/1002) and 4% by qPCR (P. falciparum 21/1002; P. vivax 16/1002, mixed: 5/1002). Infections were highly clustered, with 64% (27/42) of infections occurring in only two Pahari groups, the Khumi and Mro. Diversity was high; expected heterozygosity was 0.93 for P. falciparum and 0.81 for P. vivax. 85.7% (18/21) of P. vivax and 25% (5/20) of P. falciparum infections were polyclonal. No population structure was evident for either species, suggesting high transmission and gene flow among Pahari groups. Conclusions High subclinical infection prevalence and genetic diversity mirror ongoing transmission. Control activities should be specifically directed to Pahari groups at greatest risk.